2008
DOI: 10.1002/anie.200705516
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Oxygen Distribution in Operating Fuel Cells

Abstract: Fuel cells are devices that produce electric power by means of the chemical reaction of oxygen and fuels more efficiently than current technologies, and they are expected to become a cleaner source of energy. [1][2][3][4] Despite considerable recent advances, especially in polymer electrolyte membrane fuel cells (PEMFCs), existing technology still has drawbacks, including kinetic limitations on the oxygen reduction reaction [5,6] and the instability of Pt catalysts and polymer membranes nearby, in particular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 24 publications
(32 reference statements)
1
39
0
Order By: Relevance
“…Significant progress has been made in visualization of the spatial distribution of metal oxidation states inside a single catalyst particle by the scanning nano-XAFS technique [44]. Three dimensional spatial visualization of PEFCs in a non-destructive manner has become a state-of-the-art topic for understanding various phenomena in MEAs relevant to the performance and property of PEFCs [45][46][47][48][49][50]. We carried out the first 4D visualization of structures and chemical states of a Pt/C cathode electrocatalyst layer in PEFC MEA by a newly developed X-ray computed laminography (XCL)-XAFS method combining 3D XCL imaging and XAFS spectroscopy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress has been made in visualization of the spatial distribution of metal oxidation states inside a single catalyst particle by the scanning nano-XAFS technique [44]. Three dimensional spatial visualization of PEFCs in a non-destructive manner has become a state-of-the-art topic for understanding various phenomena in MEAs relevant to the performance and property of PEFCs [45][46][47][48][49][50]. We carried out the first 4D visualization of structures and chemical states of a Pt/C cathode electrocatalyst layer in PEFC MEA by a newly developed X-ray computed laminography (XCL)-XAFS method combining 3D XCL imaging and XAFS spectroscopy [21].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of oxygen supply to the cathode is one of the important factors in determining the performance of PEFC [1,2]. Oxygen is reduced at the cathode in the three-phase boundary composed of the gas, the polymer electrolyte layer and the Pt/C catalyst [1,2]. A sufficient amount of the polymer electrolyte increases the active surface area of the catalyst, providing an adequate supply of protons.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as far as operating PEFC with air, the reduction current can be frequently limited by the oxygen depletion [3][4][5]. Our previous report on an oxygen sensing material demonstrated that oxygen is indeed depleted at the end of gas-flow channel [2]. One way to enhance the oxygen reduction current is to apply pure oxygen to the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8], but also the catalyst's local structure and its stability. The size, shape and morphology of carbon-supported Pt nanoparticles, the most common PEM FC catalyst so far, are important physical quantities directly affecting catalyst performance.…”
Section: Introductionmentioning
confidence: 99%